DIGITAL INCLUSION AND THE MAIN CHALLENGES IN THE BRAZILIAN EDUCATION - Prioste, Claudia [UNESP]; Raica, Darcy (Unesp-faculdade Ciencias & Letras, 2017)
The access to Information and Communication Technologies (ICT) has increased within the Brazilian population. However, according to the digital inclusion ranking established by ITU (2015), Brazil still presents important gaps in comparison to other evaluated countries. In view of this problem, the present article aims at analyzing the challenges of the digital inclusion in the Brazilian education, looking into understanding its obstacles. This study has grounds in a qualitative, exploratory research methodology, through which data of national and international researches were collected. The analysis was established based in seven indicators: connectivity, capability, content, confidence, continuity, literacy, and the inclusion of people with disabilities. The results suggest that the digital inclusion has been limited, mostly due to problems in the education quality. Without a consistent educational background, the use of ICTs is mostly directed to consumption and entertainment. It was concluded that Brazilian public schools face serious gaps of technological infrastructure and teacher support. In this context, the exclusion of people with disabilities also perpetuates. Problems in the basic literacy processes are important obstacles for proper technological resources appropriation in favor of better life conditions and social participation.
Keywords: Digital inclusion; Digital literacy; Information and communication technologies; Digital divide; Technology and education